Globalisasi dan Degradasi Moral Generasi Muda Indonesia: Tinjauan Literatur dalam Perspektif Pendidikan Karakter - Erna Amalia (At-Tafakkur: Journal of Islamic Studies, 2026)
Globalization has brought significant changes to various aspects of Indonesian society, particularly through the rapid development of digital technology and social media. While globalization provides easier access to information and communication, it also poses challenges to moral values, especially among younger generations. This study aims to analyze the impact of globalization on moral degradation in Indonesian society and to examine the role of character education and family involvement in addressing these challenges. The study employed a qualitative approach using a literature review method. Data were collected from relevant scholarly articles, books, and academic sources and analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that globalization, particularly through the internet and social media, contributes to changes in behavior, values, and character among young people. Moral degradation is reflected in the decline of responsibility, discipline, and courtesy, as well as increased exposure to inappropriate content that conflicts with national cultural and moral values. The study further reveals that character education based on Pancasila values and active parental involvement play a strategic role in strengthening the moral resilience of younger generations amidst globalization. The novelty of this study lies in its synthesis of the interrelationship between digital globalization, character education, and family roles as three key elements in preventing moral degradation. Therefore, collaboration among families, schools, and communities is essential to reinforce the character of young generations and preserve national moral values in the era of globalization.